Construction of self‐cloning industrial brewer's yeast with SOD1 gene insertion into PEP4 prosequence locus by homologous recombination. Issue 2 (21st April 2016) - Wu, Deguang; Chen, Yefu; Li, Chaoqun; Lu, Jun; Liu, Yanwen; Zhang, Cuiying; Dong, Jian; Xiao, Dongguang
Abstract : Superoxide dismutase (SOD, encoded by SOD1 ), which can scavenge active oxygen free radicals, is an ideal endogenous antioxidase in beer. In this study, the SOD1 expression cassette was constructed, and this cassette contained the PGK1 promoter, the PGK1 terminator and the SOD1 gene fused to the signal sequence of the yeast mating pheromone α ‐factor ( MFα1s ). One of the prosequences of the PEP4 gene (encoding proteinase A, PrA) in Saccharomyces cerevisiae strain S‐6 was replaced by the SOD1 expression cassette via homologous recombination and the self‐cloning strain S54PS, which could improve the antioxidant capability and foam stability of beer, was successfully obtained. Fermentation results showed that the SOD activity of the final beer brewed with S54PS was increased by 21.06%. Accordingly, the DPPH‐radical scavenging activity of S54PS increased by 30.6% compared with that yielded by the parental strain S‐6. Furthermore, the PrA activity of S54PS was always lower than that of the parental strain at all stages of beer fermentation. The head retention of the beer (255 ± 4 s) was better than that of the parental strain (224 ± 1 s). Hence, this research implies that S54PS exhibits good brewing performance and can be applied to improve the industrial brewing process. Copyright © 2016 The Institute of Brewing & Distilling